THE MICRO PPM POLICY FOR MICRO SMALL MEDIUM ENTERPRISES (MSME) PERFORMERS AT THE TIME OF THE COVID-19 PANDEMIC (A CRITICAL ETHNOGRAPHIC STUDY) - Sri Andika Putri; Hendrik Suhendri; Risna Ningsih (International Journal of Multidisciplinary Research and Literature, 2022)
The Covid-19 pandemic has disrupted not only the business performance of the large business sector but also has implications for the MSME sector. This research was conducted to develop the concept of the meaning of the Micro PPM Policy among MSME actors in the city of Malang under the values, ideas, and business practices carried out by MSME actors. Besides looking for a "cultural theme" related to the implications of Micro PPM policy, this effort also aims to incorporate values originating from the business philosophy of MSME actors in managing their business to create a complete conceptual framework regarding the impact of implementing Micro PPM policies. PPM policies. The research method uses descriptive qualitative, based on the philosophy of postpositivism in which the researcher acts as a key instrument in this research. The PPM Micro policy is considered to be lacking in providing solutions to the problems faced by MSMEs during the pandemic. Discrimination in terms of distribution of aid funds. Some MSME owners feel they do not need to provide data as a requirement because those who receive aid funds are not those who have already filled in the data but certain MSMEs that government officials have appointed